2014
DOI: 10.1534/genetics.114.168344
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Demography and Long-Term Selection on the Accuracy of Genomic Prediction with Sequence Data

Abstract: The use of dense SNPs to predict the genetic value of an individual for a complex trait is often referred to as "genomic selection" in livestock and crops, but is also relevant to human genetics to predict, for example, complex genetic disease risk. The accuracy of prediction depends on the strength of linkage disequilibrium (LD) between SNPs and causal mutations. If sequence data were used instead of dense SNPs, accuracy should increase because causal mutations are present, but demographic history and longter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 59 publications
(97 reference statements)
2
88
4
Order By: Relevance
“…To inform the simulation of sequence data for the founders of this population, we relied on the work of Macleod et al (2012A), which used multilocus patterns of LD in whole-genome sequence from two Holstein founder bulls (Larkin et al, 2012) to reconstruct population genetic history. Based on this population history (with variable effective population size), Macleod et al (2012B) simulated sequence data that closely matched the multilocus LD patterns in the founder bull sequences. We observed that patterns of multilocus LD in dense SNP data from Belgian Blue cattle were very similar to Holsteins.…”
Section: Data Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…To inform the simulation of sequence data for the founders of this population, we relied on the work of Macleod et al (2012A), which used multilocus patterns of LD in whole-genome sequence from two Holstein founder bulls (Larkin et al, 2012) to reconstruct population genetic history. Based on this population history (with variable effective population size), Macleod et al (2012B) simulated sequence data that closely matched the multilocus LD patterns in the founder bull sequences. We observed that patterns of multilocus LD in dense SNP data from Belgian Blue cattle were very similar to Holsteins.…”
Section: Data Simulationmentioning
confidence: 99%
“…We observed that patterns of multilocus LD in dense SNP data from Belgian Blue cattle were very similar to Holsteins. Therefore, we used data simulated by Macleod et al (2012B) with Fregene (Chadeau-Hyam et al, 2008) as sequence data for founders of our Belgian Blue cattle population. Figure 1 describes the overall simulation scheme.…”
Section: Data Simulationmentioning
confidence: 99%
“…However, as has been shown by BrØndum et al (2015), a change in accuracy may be limited to a 1% to 5% increase. MacLeod et al (2014) showed that a benefit from the use of sequence data mainly can be achieved in populations with a large effective population size and/or a comparatively low level of LD while in populations like the Holstein population, an increase of accuracy for genomic breeding values may only be very small. Both conditions, a large effective size and a low level of LD, hence are not fulfilled for typical small populations as seen in livestock.…”
Section: Relevance Of Linkage Disequilibrium and Relationship Levelmentioning
confidence: 99%
“…A number of simulation and empirical studies have shown that increasing the number of markers may improve the predictive accuracy as N e also increased [9,[21][22][23]. However, increasing the number of markers in small N e populations provides little or no improvement on predictive accuracy [24,25].…”
Section: Introductionmentioning
confidence: 99%